Changes of nitrogen metabolism enzyme activities and protein content in response to low light during the seed filling stage in rice - XU Guangli; LIU Jia; LIANG Chenggang; WANG Yan; DING Chunbang; LI Tian (浙江大学学报. 农业与生命科学版, 2016)
Light condition is one of the important factors affecting plant growth. During plant growth, light deficiency will result in the decrease in carbon fixation, photosynthetic efficiency, and leaf senescence acceleration, and thus decrease yield evidently. Besides yield, light also affect the rice qualities through influencing the seed compositions such as protein. Many studies have been carried out to evaluate the effect of light on protein synthesis. For example, previous studies have been certified that the protein accumulation is increased during the seed filling stage, as well as amino acids. The enzymes of glutamine synthetase (GS), glutamic oxalo-acetic transaminase (GOT), and glutamate pyruvate transaminase (GPT) are considered as the key enzymes regulating the synthesis of protein. Almost 95% of N was absorbed through GS/glutamate synthetase (GOGAT) cycle in plants and converted into glutamic acid (Glu) and glutamine (Gln). The Glu and Gln are then converted into other amino acids which provide the precursor materials for protein synthesis through the transamination reactions of GOT and GPT. However, researches about the effect of the activities of GS, GOT and GPT on amino acid and protein synthesis of rice are limited, especially under stress conditions such as low light.Based on previous studies, we carried out this experiment to evaluate the effect of low light on key enzyme activities of nitrogen metabolism and protein accumulation during the seed filling stage. The aims of this study were to study the dynamic changes of GS, GOT and GPT under different low light conditions during the seed filling stage, and evaluate the relationships between the activities of enzymes and protein accumulation.The experiment was initiated at Sichuan Agricultural University, Ya’an, China, in 2013. Four cultivars including japonica cultivars Akitakomachi and Koshihikari, indica cultivar IR72, and hybrid indica cultivar Gangyou 527 were selected as the materials. All the cultivars were managed routinely till the flowering stage, then 25% shading (A1) and 50% shading (A2), were set respectively as the treatments till maturity by using shade net, and natural condition was set as CK. Each treatment plot was repeated 3 times and the rice panicles which grown uniformly were marked for further sample collection. After 10 days of treatments, the seed samples were collected per 7-day period till maturity and stored in freezer at -80 ℃. After harvest, the samples were used to measure GS, GOT and GPT activities, as well as soluble protein, total protein and amino acid contents.Results showed that the GS activities were significantly decreased by 20.01%-30.52% at A2 than A1 (11.61%-19.36%) compared with CK, whereas, the activities of GOT and GPT increased significantly at A2 (GOT increased by 26.07%-36.82% and GPT increased by 26.07%-61.07%) than A1 (GOT increased by 14.02%-23.02% GPT increased by 11.81%-33.83%) compared with CK. In consistent with GOT and GPT, patterns of soluble protein, total protein, as well as amino acids were also significantly increased under low light conditions especially at A2 (compared with CK, soluble protein increased by 31.19%-70.51%, total protein increased by 16.02% 28.89%, and amino acids increased by 16.04%-22.48% at A2). The correlation analysis showed that GS activity was negatively correlated to soluble protein, total protein and amino acids under low light conditions, however, GOT and GPT showed positive correlations with soluble protein, total protein and amino acids.Based on the results, we speculated that the synthesis of protein of rice grain was more significantly affected by GOT and GPT which tended to increase the accumulation of both protein and amino acids, compared with GS. In addition, in consistent with previous studies, the low light conditions were beneficial for protein and amino acid synthesis of rice grain during the seed filling stage.